Field of study choice: using conjoint analysis and clustering. Issue 2 (13th March 2017) - Shtudiner, Ze'ev; Zwilling, Moti; Kantor, Jeffrey
Abstract : Purpose: The purpose of this paper is to measure student's preferences regarding various attributes that affect their decision process while choosing a higher education area of study. Design/methodology/approach: The paper exhibits two different models which shed light on the perceived value of each examined area of study: conjoint analysis and clustering k-means algorithm. Findings: The findings of the used methods exhibit not only which of the attributes have the greatest influence on students' decision-making process, but also shed light on which types of study areas are most preferred by respondents. Originality/value: The paper addresses a new view on students' definition of higher education when adding the choice of selecting the "proper" area of study to one's profile.